1997
DOI: 10.1088/0953-2048/10/9/012
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and x-ray pole-figure characterization of DC-sputtered Bi-2201, Bi-2212 and Bi-2223 thin films

Abstract: Thin films of the three members of the superconducting series Bi 2 Sr 2 Ca n−1 Cu n O 2n+4 , n = 1, 2, 3, were prepared by diode sputtering. X-ray characterization shows that all the films are single phase and c-axis oriented and in addition they are epitaxially grown. The latter is found by x-ray pole-figure measurements taken with a four-circle diffractometer. These are emphasized in this work. AC susceptibility measurements show that, while the 2201 films are not superconducting until 4 K, the transition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
1
6
0
1
Order By: Relevance
“…On the other hand, a T zero c = 105 K and a sharper transition was obtained in Bi,Pb-2223 thin film after annealing. This confirms that sputtering deposition and annealing is an effective means of obtaining high quality of Bi,Pb-2223 thin films, as has been previously reported [4]- [6]. The importance of annealing temperature on the microstructure and superconducting properties of the films is demonstrated by the XRD data shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, a T zero c = 105 K and a sharper transition was obtained in Bi,Pb-2223 thin film after annealing. This confirms that sputtering deposition and annealing is an effective means of obtaining high quality of Bi,Pb-2223 thin films, as has been previously reported [4]- [6]. The importance of annealing temperature on the microstructure and superconducting properties of the films is demonstrated by the XRD data shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…The films are single phase and have their c-axis normal to the film surface, as was revealed by x-ray θ -2θ scans [11]. In addition, the films are fully epitaxial, which was checked by extensive single-crystal diffraction measurements [11] and confirmed by polarized micro Raman spectroscopy [12] [11].…”
Section: Superconducting Thin Films Of Bimentioning
confidence: 82%
“…C substrate temperature and 3 mbar pressure of pure oxygen. Details of the experimental conditions can be found in [11].…”
Section: Introductionmentioning
confidence: 99%
“…3 Thin film work has shown that stacking faults in the structure induce broadening and displacement of the X-ray diffraction peaks. 4 Moreover, a huge background, usually called "glassy phase" 5 usually accompanies the measured spectra.…”
Section: Introductionmentioning
confidence: 99%